Sosialisasi dan Pelatihan Pemanfaatan E-Commerce Untuk Meningkatkan Kuantitas dan Kualitas Produk Minyak Angin Aroma Terapi Bagi Pelaku UMKM Di Kelurahan Sewu - Isawati, Isawati; Wicaksono, Erlangga Adji; Hertanto, Alfario Putra; Widyastuti, Annisa Nur; Salsabiila, Fa’ari; Kusumawatie, Ghuvin Fitri; Juniarti, Irna Retno; Avivi, Jenny Anatasia; Agustina, Jesicca Mayang; Sumayyah, Najmi; Ernamasari, Navalia Dewi (Society : Jurnal Pengabdian Masyarakat, 2023)
Micro, Small, and Medium Enterprises (MSMEs) make a substantial contribution to the economic downturn resulting from the COVID-19 pandemic. The COVID-19 pandemic has had a major impact on the largest economic crisis in Indonesian history, especially in the Sewu Village. MSMEs play an important role in stabilizing the economy, but in their efforts, it is necessary to collaborate with technological developments to keep up with the times. Marketing strategies also affect MSMEs. Marketing strategies can use online media such as social media and e-commerce, which can help improve the quality of marketing for MSMEs themselves. It is hoped that the training for making aromatherapy oil can trigger the spirit to create MSMEs and market products with the help of social media.